FROM COMPLIANCE TO BENEFIT: SHARIA ACCOUNTING PRACTICES AT BMT NU TEMAYANG - Ulfatul Khasanah (Universitas Islam Negeri Sumatera Utara Medan, 2025)
This study aims to examine the shift in the This study was conducted through a qualitative approach with a case study design at Baitul Maal wat Tamwil (BMT) NU Temayang, Bojonegoro Regency, which represents a financial institution based on Nahdlatul Ulama's socio-religious values. Data collection was conducted through in-depth semi-structured interviews with managers, accounting staff, the Sharia Supervisory Board, and BMT members, supplemented by participant observation and document analysis in the form of financial reports and social reports. The data analysis process used thematic analysis with a maqashid sharia framework, through the stages of data reduction, data presentation, and conclusion drawing. The results of the study identified three main themes, namely: (1) the meaning of compliance with PSAK Sharia as a form of religious mandate; (2) the function of accounting as a means of establishing justice and social trust; and (3) welfare as the final orientation in sharia financial practices. These findings indicate that sharia accounting practices at BMT NU Temayang are not limited to administrative activities, but rather serve as social and spiritual practices that reflect moral responsibility to Allah SWT, humanity, and the community. From a theoretical perspective, this research enriches the development of Shariah Enterprise Theory by emphasizing the concept of maqashid-based accountability